Faithful Shep : The Story of a Hero Dog and the Nine Texas Rangers Who Saved Him - DeNevi, Don, 1937- (Book collections on Project MUSE., 2017)
Historical fiction based on a true account of the rescue of a black shepherd dog named Shep by a company of Texas Rangers in the lawless, Apache-plagued border region of 1880s West Texas.